PENGARUH INDEPENDENSI AUDITOR KOMITMEN ORGANISASI DAN GAYA KEPEMIMPINAN TERHADAP KINERJA AUDITOR - Kurniasari, Dian (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2016)
This study examines the direct influence of auditor independence,organizational commitment, and leadership style on auditor performance.Quality KAP performance is highly determined by the performance of theauditor, ideally in carrying out its profession, the auditor must also adhere tothe rules of professional ethics. Success and performance of a person in a fieldof work much determined by the level of competence, professionalism as wellas commitment to the field dilekinya. Sampling is determined by usingRandom Sampling method, so that using 33 respondents data Auditoryangworking in some KAP, The results show that the independence of auditors,Organizational commitment and leadership style have a positive andsignificant impact on auditor performance